1999
DOI: 10.1115/1.2826015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of Transitional Features of Turbulent Forced Gas Flows in Circular Tubes With Strong Heating

Abstract: In order to treat strongly heated, forced gas flows at low Reynolds numbers in vertical circular tubes, the k-ε turbulence model of Abe, Kondoh, and Nagano (1994), developed for forced turbulent flow between parallel plates with the constant property idealization, has been successfully applied. For thermal energy transport, the turbulent Prandtl number model of Kays and Crawford (1993) was adopted. The capability to handle these flows was assessed via calculations at the conditions of experiments by Shehata (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…While Mikielewicz [1994] demonstrated that a number of popular turbulence models produce poor predictions in this regime, he also showed that the k-model of Launder and Sharma [1974] is satisfactory. For the complex turbulent and laminarizing flows induced by strong heating of a gas flow in this range, several turbulence models have been shown to give good predictions [Kawamura, 1979;Ezato et al, 1999;Nishimura et al, 2000]. Satake [1996] has extended his Direct Numerical Simulation technique to flow in a circular tube [Satake and Kunugi, 1998].…”
Section: Related Workmentioning
confidence: 99%
“…While Mikielewicz [1994] demonstrated that a number of popular turbulence models produce poor predictions in this regime, he also showed that the k-model of Launder and Sharma [1974] is satisfactory. For the complex turbulent and laminarizing flows induced by strong heating of a gas flow in this range, several turbulence models have been shown to give good predictions [Kawamura, 1979;Ezato et al, 1999;Nishimura et al, 2000]. Satake [1996] has extended his Direct Numerical Simulation technique to flow in a circular tube [Satake and Kunugi, 1998].…”
Section: Related Workmentioning
confidence: 99%
“…The k-ε turbulence model of Abe, Kondoh and Nagano [1994], developed for forced turbulent flow between parallel plates with the constant property idealization, has been successfully extended by Ezato et al [1999]. For thermal energy transport, the turbulent Prandtl number model of Kays and Crawford [1993] was adopted.…”
Section: Before They Can Be Applied With Confidence To Gas-cooled Sysmentioning
confidence: 99%
“…Special attention was given to properly reproduce the near-wall asymptotic behavior. The second full LR model (further denoted as Ezato [8]) is a recent improvement of existing LR thermal entry-flow models that has been validated in strongly laminarizing turbulent channel flows. In all models, the turbulent species Schmidt numbers were 0.9, C l ‫ס‬ 0.09, and C e2 ‫ס‬ 1.0.…”
Section: Turbulence Modelingmentioning
confidence: 99%
“…[21]). At the wall ( y ‫ס‬ 0), the measured temperature profile (average between both plate distributions) was used as energy boundary condition; in both full LR models ‫ס‬ at y ‫ס‬ 0 [8,20].…”
Section: Numerical Approachmentioning
confidence: 99%
See 1 more Smart Citation